Exploring nurse preceptors' perceptions of benefits and support of and commitment to the preceptor role in the Western Cape Province - Inez S. Cloete; June Jeggels (AOSIS, 2014)
Background: A preceptor is a specialised tutor who provides practical training to students in the practice setting. They are frequently used to orientate nursing students to prepare them for their duties as professional nurses. In the Western Cape Province professional nurses attend a training programme to prepare them for the role of preceptor. After completion of the training it is unclear how the trained nurse preceptors perceive their preparation for the role. The perceptions of preceptors may influence their commitment to their role. Objective: The purpose of this study was to explore nurse preceptors' perceptions of benefits, support and commitment to the preceptor role. A conceptual framework guided the study which replicated previous studies that explored nurse preceptors' perceptions. Method: A quantitative approach utilising a descriptive correlational design was used in this study to address the research questions. A convenience sample was drawn from preceptors (n = 60) who had completed a preceptor training programme at the University of the Western Cape. Instrumentation for the study included the following scales: preceptors' perceptions of benefits and rewards, preceptors' perceptions of support, and commitment to the preceptor role. Data analysis was performed using SPSS 20.0. Results: The findings indicate that nurse preceptors were committed to their role. Conclusion: The findings of this study are supported by Kanter's model of structural determinants of behaviour in organisations, since preceptors who see themselves as having access to opportunity and support are likely to be committed to their role.